Without warning - Rosenberg, Joel C. 1967- (Thorndike, Maine Center Point Large Print, 2017)
When the president erroneously believes that ISIS is about to be defeated, foreign correspondent J.B. Collins informs him he is wrong and argues for a capture, or kill, order for the leader, Abu Kahlif.
Originally published: Carol Stream, Ill. : Tyndale House, 2017.
104915
Keywords: IS (Organization); Journalists -- Fiction; Large type books; Christian fiction; Suspense fiction; Religious fiction; Thrillers (Fiction)